Potential regional productivity and greenhouse gas emissions of fertilized and irrigated switchgrass in a Mediterranean climate - Lee, Juhwan; Pedroso, G.; van Kessel, C.; Six, J. (2015)
The potential of switchgrass (Panicum virgatum L.) to offset large-scale greenhouse gas (GHG) emissions depends on optimizing external inputs when the crop is primarily managed as a sustainable source for renewable energy production. Due to the heterogeneity of climate and soil conditions and the complexity of agriculture, an evaluation of the effect of adopting switchgrass as a new biofuel crop into agriculture needs to be done at the regional scale. The objective of the study was to predict long-term (100-yr) GHG emissions under different N fertilization (0, 112, and 224 kg N ha−1) and irrigation application (0, 25, 50, 75, and 99 cm H2O) levels across the Central Valley of California using the DAYCENT model. Six cultivars (Alamo, Kanlow, Cave-in-Rock, Blackwell, Sunburst, and Trailblazer) were selected. The model results suggest that switchgrass productivity is primarily constrained by N inputs when no or low water stress is expected in a Mediterranean climate. In the short-term (the first decade after establishment), soil organic carbon (SOC) stocks (0–20 cm) increased by 0.42–0.92 Mg C ha−1 yr−1 and N2O emissions were 1.37–2.48 kg N2O–N ha−1 yr−1 across the cultivars with baseline input rates of 224 kg N ha−1 yr−1 and 99 cm H2O. All cultivars were net CO2 sinks in the near term and the potential decreased by 0.09–0.30 Mg C ha−1 yr−1 (15.5–52.8%) with reduced N input from baseline under varying irrigation rates. There was a reduction in N2O emissions by 47.2–61.6% by applying less N fertilizer when irrigated at rates ≥75 cm H2O per year over time. In general, higher-yielding cultivars (e.g., Alamo) tended to sequester more CO2 but also led to higher N2O emissions. In the near term, the use of N fertilizer and irrigation is needed for switchgrass systems to be a soil GHG sink, but for longer-term GHG mitigation strategies reducing both N fertilization and irrigation inputs is required.